Examining Ghanaian Lower Secondary School Science Test through Revised Bloom’s Taxonomy - Stephen Adofo; Sirpa Kärkkäinen; Tuula Keinonen (Science Education International, 2024)
This study examined integrated science questions of the Basic Education Certificate Examination (BECE) in Ghana at the end of grade 9. Results from BECE determine which senior high school a student can attend. Science questions (n = 751) over the span of eight years were analyzed in this study and viewed under the lens of the revised Bloom’s Taxonomy using content analysis. Results show that the majority of the test questions fall under the categories of remembering facts and understanding issues in the revised Bloom’s Taxonomy. There were fewer questions related to applying acquired knowledge and analyzing or evaluating issues. Test questions did not include items testing the creation of new knowledge or related combinations. Questions were proportionally distributed across agriculture and environmental science, and the natural sciences (biology, physics, and chemistry). The test also contained several inquiry-related questions distributed across the taxonomy levels and various disciplines. Inquiry questions spanned remembering, understanding, applying, analyzing, and evaluating with most questions belonging to remembering and understanding. By emphasizing higher-order thinking skills such as analysis, evaluation, and creation in test questions, it is possible that the test may direct science education to enhance students’ competencies in their personal and professional lives.